The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1111/apt.13469
|View full text |Cite
|
Sign up to set email alerts
|

Review article: inhibition of methanogenic archaea by statins as a targeted management strategy for constipation and related disorders

Abstract: SummaryBackgroundObservational studies show a strong association between delayed intestinal transit and the production of methane. Experimental data suggest a direct inhibitory activity of methane on the colonic and ileal smooth muscle and a possible role for methane as a gasotransmitter. Archaea are the only confirmed biological sources of methane in nature and Methanobrevibacter smithii is the predominant methanogen in the human intestine.AimTo review the biosynthesis and composition of archaeal cell membran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0
8

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(56 citation statements)
references
References 63 publications
1
46
0
8
Order By: Relevance
“…The growth rate decreased by 50% in 10-20 nM simvastatin lactone. This concentration was within the range of app K i of simvastatin lactone for the purified enzyme activity measurements in this work but was much lower than the lovastatin (a statin) concentration (4-10 lM) required for 50% inhibition of the methanogenic archaea that inhabit rumen (i.e., Methanobrevibacter) [32,33].…”
Section: Kinetic Properties Of Mhmgrmentioning
confidence: 67%
“…The growth rate decreased by 50% in 10-20 nM simvastatin lactone. This concentration was within the range of app K i of simvastatin lactone for the purified enzyme activity measurements in this work but was much lower than the lovastatin (a statin) concentration (4-10 lM) required for 50% inhibition of the methanogenic archaea that inhabit rumen (i.e., Methanobrevibacter) [32,33].…”
Section: Kinetic Properties Of Mhmgrmentioning
confidence: 67%
“…By the way, methanogenic bacteria may also be targeted using SYN‐010, a modified release statin . One study demonstrated that 4 weeks of SYN‐010 in IBS patients to reduce methane levels from baseline as well as to improve abdominal pain and stool frequency …”
Section: Antibiotics—neomycinmentioning
confidence: 99%
“…64 One study demonstrated that 4 weeks of SYN-010 in IBS patients to reduce methane levels from baseline as well as to improve abdominal pain and stool frequency. 62 The treatment of IBS symptoms may benefit from certain antibiotics, however, antibiotics may even contribute toward the initial onset of IBS symptoms. There is an association between prior macrolide (P = .036) and tetracycline (P < .025) use within 12 months of a new diagnosis of IBS.…”
Section: Mixed Probioticsmentioning
confidence: 99%
“…El otro aspecto interesante es la presencia de una línea plana en las pruebas de aliento, explicada también en los ejemplos que se presentan. Esta línea plana puede ser debida a la presencia de bacterias que consumen hidrógeno y, como resultado, las archaeas son incapaces de producir metano, cuyo principal substrato es el hidrógeno 21 . El artículo revisa además la utilidad de las pruebas de aliento en aplicaciones menos conocidas como el vaciamiento gástrico y la DF.…”
unclassified